Tertiary nautiloids from Patagonia, southern Argentina (Ameghiniana, 2014)
Nautiloids are represented in the Tertiary of Argentina by four genera and six species: Eutrephoceras sp., Hercoglossa rionegreneis Reichler, Hercoglossa romeroi (Ihering), Hercoglossa aff. H. walteri Miller, and Ci1110miacamachoi Masiuk, from the Paleocene Roca, El Fuerte and Salamanca formations, and Aturia carotiameghinoi (Ihering), from the Eocene-Oligocene San Julián Formation. A shallow habitat is proposed for Hercoglossa aff. H. uxilteri. Paleoenvironmental conditions for the Argentinian Tertiary nautiloids were most favorable during the Danian; five species are known. The subclass Nautiloidea is not recorded in Argentina in post-Oligocene rocks.